Storage behaviour of exotic potato genotypes and hybrid clones under natural condition - Akhter, Sajeda; Islam, Md. Monirul; Naher, Laila; Alam, M. Shamsul; Khatun, M. Majida; Yusuf, Umi Kalsom (Gaurav Society of Agricultural Research Information Centre, 2014)
An experiment was conducted to evaluate the storability of hybrid clones and exotic genotypes at room temperature during April to August 2011 and April to August 2012. Fourteen hybrid clones and 14 exotic genotypes were stored for five months at ambient temperature. Hybrid clones 7.33 and 7.12 showed better performance in respect of storage behaviour (minimum weight and rottage loss) at ambient temperature. The maximum storability was found in Labadia, Liseta, Albaata, Lambada and Amanda exotic genotypes. Moreover, hybrid clones 7.33 and 7.12 exhibited minimum weight and rottage loss in both the hybrid clones and the exotic genotypes. Based on their storage behaviour at ambient temperature, it may be concluded that hybrid clones 7.33 and 7.12 are found to be suitable for storage under ordinary room temperature conditions for a period of 90 to 120 days and slow release to market for avoiding distress sale.